2008
DOI: 10.1007/s10648-008-9078-3
|View full text |Cite
|
Sign up to set email alerts
|

An Interdisciplinary Model of School Absenteeism in Youth to Inform Professional Practice and Public Policy

Abstract: Problematic school absenteeism in youth has long been a complex and vexatious issue for psychologists, educators, and researchers from other disciplines. An examination of problematic school absenteeism from different perspectives over many decades has led to poor comparability across publications, policies, and assessment and intervention protocols. This article briefly reviews literature from psychology, social/criminal justice, and education to outline important factors that influence school absenteeism. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
207
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(222 citation statements)
references
References 157 publications
(146 reference statements)
9
207
1
5
Order By: Relevance
“…The findings of this study is further supported by [18] whose study on Causes and structural effects of student absenteeism: a case study of three South African Universities revealed a multifactorial cause. Studies by [19]; [20] also lend their support to the findings of this study.…”
Section: Factors Influencing Absenteeism Among Nursing Studentssupporting
confidence: 82%
“…The findings of this study is further supported by [18] whose study on Causes and structural effects of student absenteeism: a case study of three South African Universities revealed a multifactorial cause. Studies by [19]; [20] also lend their support to the findings of this study.…”
Section: Factors Influencing Absenteeism Among Nursing Studentssupporting
confidence: 82%
“…Bei Weitere wünschenswerte Schritte zukünftiger Forschung sind in einem integrativerem und fächerübergreifenden Forschungsansatz sowie einer stärkeren Betonung des Zusammenwirkens einzelner Faktoren zu sehen (Ingul, Klöckner, Silverman, Nordahl, 2012;Kearney, 2008). Da Schulabsentismus als komplexes Problem zu verstehen ist, sollten kindbezogene, schulbezogene und familiäre Faktoren berücksichtigt, verbunden und in Beziehung zueinander statt unabhängig voneinander untersucht werden.…”
Section: Zusammenhang Von Schulabsentismus Mit Emotionalen Und Verhalunclassified
“…Some children may be able to attend school in some instances but choose to stay at home with the full knowledge that their parents are under scrutiny for their school refusal (Lauchlan, 2003). Kearney (2008) identified four reasons for school refusal: (1) avoidance of stimuli provoking negative affectivity; (2) escape from aversive social situations; (3) pursuit of attention from significant others; and (4) pursuit of tangible rewards outside of school. Moreover, school refusers commonly combine reasons 1 and 4.…”
mentioning
confidence: 99%